Studying the Existence of Progressive Law in Handling Children Faced with the Law (Universitas PGRI Madiun, 2022)
Children are special legal subjects, judging from the legal responsibilities they have. The legal conception places children as legal subjects that are different from adults, both in the civil realm and in the realm of criminal law. Progressive law, as well as placing children as legal subjects that are special in nature, that is, they are included in